Human rights in the 'War on Terror' - Wilson, Richard, 1964- (Cambridge University Press, 2005)
This book asks whether human rights, since the 9/11 attacks and the 'war on terror, ' are a luxury we can no longer afford, or rights that must always remain a fundamental part of democratic politics, in order to determine the boundary between individual freedom and government tyranny. This volume brings together leading international lawyers, policy-makers, scholars and activists in the field of human rights to evaluate the impact of the 'war on terror' on human rights, as well as to develop a counter-terror strategy which takes human rights seriously. While some contributors argue that war is necessary in defense of liberal democracy, others assert that it is time to move away from the war model towards a new paradigm based upon respect for human rights, an internationally-coordinated anti-terror justice strategy, and a long-term political vision that can reduce the global tensions that generate a political constituency for terrorists.